Signaling credibility - choosing optimal debt and international reserves - Joshua Aizenman; Jorge Fernández-Ruiz (University of California, Santa Cruz Institute for International Economics (SCIIE), 2006)
This paper evaluates the challenges facing developing countries when there is uncertainty about the policy maker type. We consider a country characterized by volatile output, inelastic demand for fiscal outlays, high tax collection costs, and sovereign risk, where future output depends on the type of policymaker in place today. There are two policymakers - type T chooses debt and international reserves to smooth tax collection costs; type S has higher discount factor, aiming at obtaining current resources for narrow interest groups, and preferring not to undertake costly reforms that may enhance future output. Financial markets do not know the type of policymaker in place and try to infer its type by looking at its financial choices. We show that various adverse shocks (lower output, higher real interest rate, etc.) can induce a switch from an equilibrium where each policy maker chooses its preferred policy to another where T distorts its policies in order to separate itself from S in the least costly way. This is accomplished by type T reducing both international reserves and external debt. Further decline in output would induce type T to lower debt, and reserves would fall at a higher rate than otherwise expected.
Keywords: F31; F34; F36; 330; credibility; international reserves; external debt; Währungsreserven; Glaubwürdigkeit; Signalling; Auslandsverschuldung; Theorie